EVALUATING PUBLIC PRIVATE PARTNERSHIP FINANCING MECHANISMS FOR STIMULATING INVESTMENT IN TOURISM SERVICES - Abdurazakov Shavkatjon Shokirdjanovich (International Journal of Asian Economic Light, 2026)
This study establishes a dynamic empirical framework to evaluate the structural, causal, and risk-mitigating impacts of distinct Public-Private Partnership (PPP) financing mechanisms—specifically Viability Gap Funding (VGF), Minimum Revenue Guarantees (MRG), Concessional Subordinated Debt (CSD), and Availability Payment Hybrids (APH)—on private capital mobilization in tourism services infrastructure. Addressing dynamic persistence, unobserved cross-sectional heterogeneity, and endogenous concession assignment, the empirical inquiry applies a two-step System Generalized Method of Moments (System GMM) and Panel Autoregressive Distributed Lag (P-ARDL) estimation framework to a balanced panel dataset spanning 2011–2025 across 42 emerging and tourism-developing economies. The econometric findings demonstrate a statistically robust, non-linear relationship between PPP sovereign co-financing structures and private investment response. Specifically, direct capital-stage Viability Gap Funding exhibits an immediate, potent crowding-in effect (β=0.412,p